Applied Analysis of Growth, Trade, and Public Policy Ten Years of International Academic Exchanges Between JAAE and KEBA (Springer Singapore, 2018)
This book analyzes the various problems of growth, trade and public policy from the perspective of applied economics, based on research in areas such as public policies, trade and regulation, and development economics. Part 1 investigates the broad problems of growth and regional economy, focusing on economic developments in Japan and Korea. Part 2 discusses trade and foreign investment in Japan, mainly on an empirical basis. Part 3 then examines various public economic policies using applied analysis tools. The papers in this volume have been collected to commemorate ten years of academic exchange between the Japan Association for Applied Economics (JAAE) and the Korean Economics and Business Association (KEBA), and include an applied economic analysis of growth and trade in Korea and Japan.